2018
DOI: 10.1213/ane.0000000000002735
|View full text |Cite
|
Sign up to set email alerts
|

Videolaryngoscopy for Physician-Based, Prehospital Emergency Intubation: A Prospective, Randomized, Multicenter Comparison of Different Blade Types Using A.P. Advance, C-MAC System, and KingVision

Abstract: During prehospital emergency endotracheal intubation performed by emergency physicians, success rates of 3 commercially available videolaryngoscopes A.P. Advance, C-MAC PM, and KingVision varied markedly. We also found that although any of the videolaryngoscopes provided an adequate view, actual intubation was more difficult with the channeled blade KingVision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…In our study we demonstrated a first-pass success rate of 79% with DL and 95% with VL, which is comparable to the existing literature for DL but better for VL in the prehospital setting [ 10 , 11 ]. The first pass success rate for in-hospital emergency ETI ranges from 75% to 85% with DL [ 15 , 18 , 19 ], and up to 96% with VL [ 16 , 20 , 21 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In our study we demonstrated a first-pass success rate of 79% with DL and 95% with VL, which is comparable to the existing literature for DL but better for VL in the prehospital setting [ 10 , 11 ]. The first pass success rate for in-hospital emergency ETI ranges from 75% to 85% with DL [ 15 , 18 , 19 ], and up to 96% with VL [ 16 , 20 , 21 ].…”
Section: Discussionsupporting
confidence: 88%
“…Ruetzler and colleagues found different success rates in a comparison of five different videolaryngoscopes in a training situation in which C-MAC performed very well in difficult airway situations [ 27 ]. Cavus et al however, found the C-MAC only comparable to the A.P.Advance but better than the KingVision [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endotracheal intubation during cardiopulmonary resuscitation is one of the core methods of protection of airway patency [15][16][17]. In the conducted study, face-to-face intubation compared to behind-thehead intubation during the first intubation attempt was associated with lower efficacy and prolonged duration.…”
Section: Discussionmentioning
confidence: 99%
“…(b) Because of a small diameter, the bougie tends to cut across the curve of the guiding channel and pass posteriorly during passage towards the larynx, leading to failure [ 3 ]. (c) The available evidence indicates that a mismatch between the mouth opening and the device because of its bulky design is another main reason for failure of emergency intubation using the KingVision device [ 4 ]. After the bougie is shifted laterally out of the guiding channel, moreover, the anterior part of the bulky blade close to the larynx can impede advancement of the endotracheal tube along the bougie into the glottis.…”
mentioning
confidence: 99%